2009
DOI: 10.1016/j.ijrobp.2008.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Changes Mimicking New Leptomeningeal Disease After Intensity-Modulated Radiotherapy for Medulloblastoma

Abstract: Purpose-Acute and late changes in magnetic resonance imaging of the pediatric brain have been described after radiotherapy (RT). We report the post-RT neuroimaging changes in the posterior fossa after intensity-modulated RT (IMRT) in children with medulloblastoma and contrast them with those of leptomeningeal disease.Methods and Materials-We performed a retrospective review of 53 consecutive children with medulloblastoma who were treated with craniospinal RT followed by IMRT to the posterior fossa and chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
2
5
1
1
Order By: Relevance
“…4-7 However, median and mean ages at diagnosis and treatment of the patients in our series, 1.8 and 2.4 years respectively, were much younger than the median ages of 7.1 years and 8.1 years at presentation in two of those series 6,7 and mean age of 5.4 years in one of those studies. 5 Median and mean times to lesion development in our series of children post-PT is shorter than the time to appearance of photon radiation therapy -related lesions, which have been reported to arise a median of 6 to 10 months after the start or completion of radiation therapy.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…4-7 However, median and mean ages at diagnosis and treatment of the patients in our series, 1.8 and 2.4 years respectively, were much younger than the median ages of 7.1 years and 8.1 years at presentation in two of those series 6,7 and mean age of 5.4 years in one of those studies. 5 Median and mean times to lesion development in our series of children post-PT is shorter than the time to appearance of photon radiation therapy -related lesions, which have been reported to arise a median of 6 to 10 months after the start or completion of radiation therapy.…”
Section: Discussioncontrasting
confidence: 65%
“…5 Median and mean times to lesion development in our series of children post-PT is shorter than the time to appearance of photon radiation therapy -related lesions, which have been reported to arise a median of 6 to 10 months after the start or completion of radiation therapy. 4-7 The lesions in our series also tended to regress sooner (1.5 months to 3.5 months) than time interval of 2 to 26 months described for patients treated with photons. 4-7 The differences in time course may be related to the use of PT, the induction or maintenance chemotherapy regimen, the age of the patients included in our series 8,9 or other factors coincident with the performance of the protocol including surgical sequelae.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Several studies have identified treatmentrelated transient brain lesions and recommended imaging features, location, and temporal course that clearly separates them from recurrence or necrosis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The role of new techniques, for example IMRT (Intensity Modulated Radiation Therapy), tomotherapy, protontherapy, and carbon ion radiation in the reduction of doses to OARs during the irradiation of brain malignancies is under investigation [63][64][65], as well as the role of new imaging techniques [66]. Results also seem promising for medulloblastoma patients, although they should be prospectively evaluated and some reports are not completely satisfactory [63][64][65][67][68][69][70][71][72], indicating that particular attention should be given to the volumes of treatment and to the toxic effects of concomitant chemotherapy [73,74]. Despite the small number of analysed patients, our results seem to show that radiation therapy results in a good outcome without a significant negative late impact on neuropsychological abilities.…”
Section: Discussionmentioning
confidence: 99%